The emergence of collectively owned self-supply water supply systems in rural South Africa – what can we learn from the Tshakhuma case in Limpopo? - Hofstetter, Moritz; van Koppen, Barbara; Bolding, A. (Academy of Science of South Africa, 2021)
Despite the rapid extension of public service delivery since the end of Apartheid, many rural citizens in South Africa still rely on their own initiatives and infrastructure to access water. They construct, improve, operate and maintain infrastructure of different complexities, from individual wells to complex collectively owned water schemes. While most of these schemes operate without legal recognition, they provide essential services to many households. In this article we will first provide an overview of the growing international body of literature describing self-supply as an alternative pathway for public service delivery. We then take a historical perspective on the role of communities and self-supply in South Africa and describe the emergence of six collectively owned, gravity-fed, piped schemes in Tshakhuma, Limpopo Province. We describe and compare these systems using key characteristics like resource access, investment, construction, operation, maintenance and institutional governance. We further assess their performance with regard to coverage, service level, reliability, governance structure, accountability and water quality. We do so because we are convinced that lessons learned from studying such schemes as locally adapted prototypes have the potential to improve public approaches to service delivery. The described cases show the willingness of community members to engage with service delivery and their ability to provide services in cases where the state has failed. The assessment also highlights problematic aspects of self-supply related to a lack of accountability, technical expertise and the exclusion of disadvantaged community members. By describing and assessing the performance of rural self-supply schemes, we aim to recognize, study and learn from such schemes. We consequently do not conclude this article by providing answers, but by raising some pertinent, policy-relevant questions.